Innate immune receptor signaling induces transient melanoma dedifferentiation while preserving immunogenicity. Issue 6 (13th June 2022) - Thier, Beatrice; Zhao, Fang; Stupia, Simone; Brüggemann, Alicia; Koch, Johannes; Schulze, Nina; Horn, Susanne; Coch, Christoph; Hartmann, Gunther; Sucker, Antje; Schadendorf, Dirk; Paschen, Annette
Abstract : Background: Immune-stimulatory agents, like agonists of the innate immune receptor RIG-I, are currently tested in clinical trials as an intratumoral treatment option for patients with unresectable melanoma, aiming to enhance anti-tumor T cell responses. Switching of melanoma toward a dedifferentiated cell state has recently been linked to T cell and therapy resistance. It remains to be determined whether RIG-I agonists affect melanoma differentiation, potentially leading to T cell resistance. Methods: Patient metastases-derived melanoma cell lines were treated with the synthetic RIG-I agonist 3pRNA, and effects on tumor cell survival, phenotype and differentiation were determined. Transcriptomic data sets from cell lines and metastases were analyzed for associations between RIG-I (DDX58) and melanoma differentiation markers and used to define signaling pathways involved in RIG-I-driven dedifferentiation. The impact of 3pRNA-induced melanoma dedifferentiation on CD8 T cell activation was studied in autologous tumor T cell models. Results: RIG-I activation by 3pRNA induced apoptosis in a subpopulation of melanoma cells, while the majority of tumor cells switched into a non-proliferative cell state. Those persisters displayed a dedifferentiated cell phenotype, marked by downregulation of the melanocytic lineage transcription factor MITF and its target genes, including melanoma differentiation antigens (MDA). Transition into the MITF low /MDA low cell state was JAK-dependent, with some cells acquiring nerve growth factor receptor expression. MITF low /MDA low persisters switched back to the proliferative differentiated cell state when RIG-I signaling declined. Consistent with our in vitro findings, an association between melanoma dedifferentiation and high RIG-I (DDX58) levels was detected in transcriptomic data from patient metastases. Notably, despite their dedifferentiated cell phenotype, 3pRNA-induced MITF low /MDA low persisters were still efficiently targeted by autologous CD8 tumor-infiltrating T lymphocytes (TILs). Conclusions: Our results demonstrate that RIG-I signaling in melanoma cells drives a transient phenotypic switch toward a non-proliferative dedifferentiated persister cell state. Despite their dedifferentiation, those persisters are highly immunogenic and sensitive toward autologous TILs, challenging the concept of melanoma dedifferentiation as a general indicator of T cell resistance. In sum, our findings support the application of RIG-I agonists as a therapeutic tool for the generation of long-term clinical benefit in non-resectable melanoma.